CHARACTERISTICS OF THE INTEGRATIVE APPROACH IN DEVELOPING PROFESSIONAL COMPETENCE OF PHYSICAL EDUCATION TEACHERS (Scientific journal of the Fergana State University, 2024)
In this article, the characteristics of integrative approaches to the development of the professional competence of a physical education teacher include interdisciplinarity, interrelationship and complementarity, expanding and deepening, synthesizing the content of educational subjects at least at the level of SES(State Education Standart), and the highest level of form.  the interpretation of methods used in improvement, professional skills, the importance of non-traditional pedagogical technologies in the role of physical education teachers in the socio-cultural life are highlighted.